Artificial intelligence and voting advice applications - Gemenis, Kostas (Frontiers in Political Science, 2024)
The voter information tools collectively known as “Voting Advice Applications” (VAAs) have emerged as particularly popular tools in the realm of E-participation. Today, VAAs are integral parts of election campaigns in many countries around the world as they routinely engage millions of citizens, in addition to political actors and the media. This contribution assesses the integration of Artificial Intelligence (AI) in the design and dissemination of VAAs, considering normative, ethical, and methodological challenges. The study provides a comprehensive overview of AI applications in VAA development, from formulating questions to disseminating information, and concludes by highlighting areas where AI can serve as a valuable tool for enhancing the positive impact of VAAs on democratic processes.